2019
DOI: 10.1055/a-0866-9482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatigue on Functional Stability of the Knee: Particularities of Female Handball Players

Abstract: The risk of anterior cruciate ligament injury in female handball players is high. Fatigue of active stabilizers and increases in joint laxity are often mentioned in the literature as causal factors. However, no studies have been carried out on this population. Our objective is to determine the effect of muscle fatigue on active and passive knee stability in female handball players. This prospective study assessed tibiofemoral joint laxity, as well as hamstring and quadriceps strength, before (Tinitial), during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
1
10
0
2
Order By: Relevance
“…Some research has pointed that fatigue could cause acute ACL lesion [12][13][14][15][16][17][18][19][20][21][22][23] , but the de nition of ACL fatigue lesion has not been revealed completely from academic eld. Until 2013, Ashton-Miller 's biomechanical study based on knee model through donated human corpses has demonstrated that repetitive pressure-applying jump is likely to cause ACL fatigue damage, but Miller 's research is only limited in biomechanical eld, not involved with clinical research [24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Some research has pointed that fatigue could cause acute ACL lesion [12][13][14][15][16][17][18][19][20][21][22][23] , but the de nition of ACL fatigue lesion has not been revealed completely from academic eld. Until 2013, Ashton-Miller 's biomechanical study based on knee model through donated human corpses has demonstrated that repetitive pressure-applying jump is likely to cause ACL fatigue damage, but Miller 's research is only limited in biomechanical eld, not involved with clinical research [24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…This study’s salience lies in the fact that maintaining a proper trajectory is a pre-condition for the correct function of the knee joint in many life and sports activities [53]. Furthermore, all deviations from the correct knee joint trajectory signal possible joint instability [53,54] or dissynergy of muscle activities that affect the joint [55], which could be caused by fatigue [56]. Because precise motor control and being able to feel and indicate a joint’s position are crucial elements determining proper knee function, we decided to assess patients’ ability to return to flexion of 60° degrees, the speed used when re-establishing this angle, and we tested patients for any deviations from proper flexion path.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has pointed out that fatigue could cause acute ACL lesion, [14][15][16][17][18][19][20][21][22] but the definition of ACL accumulated damage has not been revealed entirely from the academic field. Not until 2013 did Ashton-Miller's biomechanical study based on a knee model demonstrate through human cadavers that repetitive pressure jumping could lead to cruciate ligament non-contact injury.…”
Section: Clinical Manifestation Of Acl Accumulated Damagementioning
confidence: 99%